Measuring resilience in a volatile world: A proposal for a multicountry system of sentinel sites - Barrett, Christopher B.; Headey, Derek D. (International Food Policy Research Institute, 2014)
We propose the development of a multicountry system of high-frequency, long-term sentinel sites in the world’s most vulnerable regions. If implemented along the lines we conceive, this system could be a high-return investment for resilience-building efforts, since it would serve multiple purposes. This system offers the only rigorous means of monitoring vulnerability and resilience in the world’s most volatile regions. This system would bolster existing early-warning systems by complementing them with household-level indicators. This system would improve the targeting of emergency resources. This system would be instrumental for diagnosing the underlying sources of vulnerability, for identifying key thresholds of resilience, and for designing appropriate resilience-building strategies. And this system would provide a rigorous foundation for large-scale evaluations of resilience-building activities.